2008
DOI: 10.1037/a0012898
|View full text |Cite
|
Sign up to set email alerts
|

Seeking professional help: Etiology beliefs about mental illness across cultures.

Abstract: In the present study, the authors examined the contributions of cultural beliefs about the etiology of mental illness to the seeking of help from mental health professionals among college students in 4 cultural groups, European Americans, Chinese Americans, Hong Kong Chinese, and Mainland Chinese. Group differences were found in help-seeking history and likelihood, with European and Chinese Americans being more likely to seek help than Hong Kong and Mainland Chinese. Multiple-group path analysis showed that la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
146
2
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(172 citation statements)
references
References 57 publications
7
146
2
5
Order By: Relevance
“…35 Thus, in a culture that emphasizes community and self-suppression, young adults feeling disconnected from others may be more vulnerable to suicidal desire. Furthermore, individuals from collectivistic cultures tend to be reluctant to discuss symptoms of mental illness and seek treatment, 36 which may exacerbate symptoms. Future research should seek to replicate this relationship across various cultures to determine the role of culture in influencing suicide risk associated with insomnia.…”
Section: Discussionmentioning
confidence: 99%
“…35 Thus, in a culture that emphasizes community and self-suppression, young adults feeling disconnected from others may be more vulnerable to suicidal desire. Furthermore, individuals from collectivistic cultures tend to be reluctant to discuss symptoms of mental illness and seek treatment, 36 which may exacerbate symptoms. Future research should seek to replicate this relationship across various cultures to determine the role of culture in influencing suicide risk associated with insomnia.…”
Section: Discussionmentioning
confidence: 99%
“…Reavley & Jorm (2014b) found that those with Bachelor's level or higher education were less likely to believe in causes other than biogenetic explanations of schizophrenia compared with those with lower education. As causal beliefs are thought to affect help-seeking behaviour (Chen & Mak, 2008;Bhikha et al 2015), public education for MHL should be delivered in a format that is easily understandable for those with less education so that they may understand the causes of mental illness and treatment options. The participants in our study were more likely to associate particular causal attributions with certain mental illnesses.…”
Section: Discussionmentioning
confidence: 99%
“…People may also avoid seeking help for mental illness or seek help from inappropriate sources based on what they believe is causing their symptoms. Chen & Mak (2008) suggested that European Americans and Chinese Americans more likely seek help from mental health professionals compared with Hong Kong Chinese and Mainland Chinese due to different lay beliefs about the causes of mental illness. Hence, causes of mental illness is one of the important topics which should be addressed in a culture-appropriate manner when educating lay people about mental illness in order to reduce stigma and help those with mental illness receive the help they need.…”
Section: Introductionmentioning
confidence: 99%
“…This was compared to family therapy (67% of cases) and individual therapy (27%) (Sze, Hou, Lan, & Fang, 2011). In addition, studies of young adults in the PRC have found a pervasive stigma attached to marital therapy services (Anderson et al, in press), in part, because seeing a mental health professional is more acceptable if the cause is perceived to be out of one's control (as with a hereditary or environmental problem), than for problems such as interpersonal difficulties (Chen & Mak, 2008). While the Chinese traditionally try to handle problems within the family (Lim, Lim, Michael, Cai, & Schock, 2010), it is plausible that increased family instability due to the rising divorce and remarriage rates may lead young adults to seek more formal, professional sources of information to deal with their marital and relationship problems.…”
Section: Help-seeking In Chinamentioning
confidence: 99%